EFEKTIVITAS PELATIHAN GAWAT DARURAT DENGAN METODE CHAIR SIDE TALK TERHADAP KEMAMPUAN IBU DALAM PENANGANAN KEJANG DEMAM ANAK - Kusno Ferianto; Dyah Pitaloka; Mei Widyawati; kusno (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Ability is a skill of an individual in mastering a skill and being used to do various tasks in a job. Mothers are the most important role in the family when children are sick and mothers tend to be unprepared to deal with children with febrile seizures. However, based on the experience of mothers in Mander Village, Tambakboyo District, shows that there has been no socialization of emergency training using the chair side talk method on the mother's ability to handle febrile seizures in children. The purpose of this study was to determine the effectiveness of emergency training with the chair side talk method on the mother's ability to treat children's febrile seizures (RT 18 RW 09 Mander Village, Tambakbooyo District). The research method used is pre-experimental, with a one-group pre-post test design. The research sample was 28 women from Mander Village, Tambakboyo District who were selected by simple random sampling. SOP research instruments and questionnaire sheets. The analysis of this study used the Wilcoxon test. The results showed that most of the mothers' abilities in dealing with children with febrile seizures before being given training were categorized as incapable, and after being given emergency training using the chair side talk method, most of them were categorized as capable. The results of statistical tests showed that there was a difference in the ability of mothers to handle febrile seizures after being given training with the chair side talk method with p-value = 0.000 at a = 0.05 (p <0.05). It is hoped that after having the child's ability to have seizures, the mother can take care of the child during a seizure